2016
DOI: 10.3758/s13414-016-1178-4
|View full text |Cite
|
Sign up to set email alerts
|

Gaze position lagging behind scene content in multiple object tracking: Evidence from forward and backward presentations

Abstract: In everyday life, people often need to track moving objects. Recently, a topic of discussion has been whether people rely solely on the locations of tracked objects, or take their directions into account in multiple object tracking (MOT). In the current paper, we pose a related question: do people utilise extrapolation in their gaze behaviour, or, in more practical terms, should the mathematical models of gaze behaviour in an MOT task be based on objects' current, past or anticipated positions? We used a data-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…It is suggested that the 100-ms lag may reflect oculomotor limits. Generally speaking, the study [18] failed to find evidence in support of motion extrapolation in MOT, as in all tested conditions gaze lagged behind the targets.…”
Section: Eye Behavior During Motmentioning
confidence: 92%
See 2 more Smart Citations
“…It is suggested that the 100-ms lag may reflect oculomotor limits. Generally speaking, the study [18] failed to find evidence in support of motion extrapolation in MOT, as in all tested conditions gaze lagged behind the targets.…”
Section: Eye Behavior During Motmentioning
confidence: 92%
“…Another interesting question about target-looking is that when observers look at targets, whether the eyes extrapolate target motion and land on a position where the target is expected to go to. Lukavský and Děchtěrenko [18] examined this question yet failed to find evidence in support of motion extrapolation in MOT. Instead, they observed that in all the tested conditions the gaze lagged behind the targets.…”
Section: Eye Behavior During Motmentioning
confidence: 99%
See 1 more Smart Citation
“…In position monitoring and tracking tasks, some report extrapolation of the representation of moving targets (e.g. Atsma et al 2012;Iordanescu et al 2009), whereas others report attention lagging behind the stimulus (Lukavský and Děchtěrenko 2016). The position monitoring variant of the MOT task (Howard and Holcombe 2008;Howard et al 2011Howard et al , 2017 is uniquely able to test for the presence of perceptual lag, that is to say the tendency of participants to report positions from the recent past instead of the most up-to-date position of targets.…”
Section: Introductionmentioning
confidence: 99%
“…In position monitoring and tracking tasks, some report extrapolation of the representation of moving targets (e.g. Atsma et al 2012 ; Iordanescu et al 2009 ), whereas others report attention lagging behind the stimulus (Lukavský and Děchtěrenko 2016 ). The position monitoring variant of the MOT task (Howard and Holcombe 2008 ; Howard et al 2011 , 2017 ) is uniquely able to test for the presence of perceptual lag, that is to say the tendency of participants to report positions from the recent past instead of the most up-to-date position of targets.…”
Section: Introductionmentioning
confidence: 99%